Occurrence of gastro-intestinal parasites among small ruminants in Malaysia : highlighting Dicrocoelium infection in goats - Tan, T. K.; Chandrawathani, P.; Low, V. L; Premaalatha, B.; Lee, S. C.; Chua, K. H.; Sharma, R. S. K.; Romano, Ngui; Tay, S. T.; Quaza, N.H.N; Lim, Y.A.L. (The Malaysian Society of Parasitology and Tropical Medicine (MSPTM), 2017)
The aim of the present study was to determine the gastro-intestinal (GI) parasitic infections among small ruminants (i.e., goats, sheep, deer) in Malaysia through formalin-ether concentration technique. Overall, 70.9% or 302 out of 426 small ruminants (79.4% or 251/316 goats; 87.5% or 35/40 sheep; 22.9% or 16/70 deer) were infected with at least one species of GI parasites. Overall, ten types of GI parasites [Helminth: strongyle (57.7%), Moniezia spp. (5.4%), Paramphistomum spp. (4.5%), Strongyloides spp. (4.2%), Dicrocoelium spp. (2.3%), Trichuris spp. (2.3%); Protozoa: Eimeria spp. (23.7%), Entamoeba spp. (18.8%), Giardia spp. (1.9%), Cryptosporidium spp. (0.2%)] were detected in this study. Among the studied animals, goats harboured the highest diversity of GI parasites (ten types), followed by sheep (six types) and deer (two types). Polyparasitism was observed in goats (43.7% or 138 of 316) and sheep (15.0% or 6 of 40). Cumulatively, a total of 32 combinations of coinfections (Helminth+Helminth: 8 combinations; Helminth+Protozoa: 20 combinations; Protozoa+Protozoa: 4 combinations) between detected parasites with up to quintuple infections were reported. Among these parasites, “strongyle + Eimeria spp.” and “Moniezia spp. + strongyle” were the commonest infections in goats (13.5% or 34 of 251) and sheep (5.7% or 2 of 6), respectively. This study is a comprehensive documentation on multiple GI parasitisms among small ruminant in Malaysia, and the findings are crucial for effective farm management, especially for the formulation of parasitic control and elimination strategies.